ʺCognitive independence of students in the context of historical and pedagogical analysisʺ - Kondrashkin , M. Y (Problems of Engineer-Pedagogical Education, 2024)
The article deals with cognitive independence as the highest form of activity and consciousness of students in the learning process, their readiness for independent cognitive activity in their future professional life in various fields of production. A historical and pedagogical analysis of the emergence and formation of the concept of "cognitive independence" as a separate phenomenon of pedagogical science is carried out, based on the analysis of philosophical, terminological, psychological and pedagogical literature and scientific works. The article identifies the peculiarities in the formation of the concept of "cognitive independence" at each historical stage, and provides a comparative characterization of the development of cognitive independence in domestic and foreign pedagogy. The article outlines the common and distinctive features in the definition of the concept of "cognitive independence" at each historical stage of its development, identifies and characterizes the mandatory factors for the development of cognitive independence, such as interest, initiative and perseverance. It is noted that the concept of "cognitive independence" in the modern context is considered as a multidimensional personal formation, which is expressed in the need for a person to perform new actions to obtain new knowledge through cognitive activity, the ability to synthesize cognitive motives and methods of independent behavior, in self-regulation of cognitive activity. The views of scientists who define cognitive independence as an integrative dynamic quality of a personality that requires a systematic approach to its analysis are studied, as well as their reasoned evidence that cognitive independence can be optimal only if it is initiated by teachers. The requirements for the organization of the educational process, compliance with which will allow the formation of cognitive independence in students in the learning process, are characterized: increasing tasks for independent work, including creative learning tasks in the learning process, creating problem situations, using creative and research methods of teaching, implementing the principles of collaborative pedagogy, developing students' ability to work with various information sources. The main features on the basis of which it can be argued that a student has formed cognitive independence are identified: awareness of the importance and necessity of the learning process itself, the ability to learn, cognitive abilities and the ability to independently form an individual learning style.